The role of corporate social investment in supporting early childhood development in South Africa - Van Niekerk, Lauren-Jayne (Department of Social Development, 2015)
This research study, The Role of Corporate Social Investment in Supporting Early Childhood Development in South Africa, explored the role of and the degree to which, corporate social investment (CSI) initiatives in South Africa support early childhood development (ECD). Trends of CSI expenditure in ECD over time were examined, as well as the motivations for investment in the ECD sector. A key intention of this study was to establish the benefits of corporate investment in the ECD sector, and to discover how the ECD sector can tap into more CSI funding in the future. This study adopted a quantitative methodology and made use of an online survey tool (SurveyGizmo) to gather information from both the CSI and ECD Non-Profit Organisation (NPO) sectors in South Africa. The sample populations consisted of CSI initiatives of 500 of South Africa's best managed companies from the TOPCO Media: Top500 publication, and 62 ECD NPOs in South Africa from a database developed by one of the leading ECD NPOs in South Africa, Centre for Early Childhood Development (Atmore, 2012).